Peningkatan Kualitas Kompos Sampah Pasar Menggunakan Mikroorganisme Lokal (MOL) Bonggol Pisang dan Dedak - Linda Noviana; Vadhila Rahmadita; Purnomosutji Dyah Prinajati (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
Traditional markets produce vegetable and fruit waste which can be used as compost because it contains good nutrition for plants. This study aimed to determine the influence and differences in the quality of organic market waste compost based on the content of C-organic, Nitrogen (N), C/N ratio, Phosphorus (P), and Potassium (K) according to SNI 19-7030-2004 regarding the Compost Specifications for Domestic Organic Waste. The design of this study was a Group Randomized Design (GRD) with nine treatments and two replications, so there were 18 observation units. The research factors were variations of MOL banana weevil consisting of 0 ml (B1), 250 ml (B2), and 500 ml (B3), and bran variations consisting of 0 kg (C1), 0,25 kg (C2), and 0,5 kg (C3). The treatment consists of B1C1, B1C2, B1C3, B2C1, B2C2, B2C3, B3C1, B3C2, and B3C3. The results showed that AB2C1 was the best treatment for the C-organic parameters (30,60%), Phosphorus (1,56%), and Potassium (0,99%), while AB3C3 was the best treatment for the C/N ratio parameters (26) and Nitrogen (1,36%). Traditional market activities generating organic waste every day, it causing a acumulation of organic waste that has the potential to cause environmental pollution. Organic waste can be used as raw material in making compost using local microorganism bioactivators (MOL) banana weevil and the addition of bran. MOL Banana weevil contains gibberellin and cytokinin growth regulator which is useful for accelerating the plant growth. Bran contains phytochemicals and vitamins that are able to enrich the chemical content of compost fertilizer. This study aims to determine the influence and differences in the quality of organic market waste compost based on the content of C-organic, Nitrogen (N), C/N ratio, Phosphorus (P), and Potassium (K) according to SNI 19-7030-2004 regarding the Compost Specifications from Domestic Organic Waste. The design of this study was a Group Randomized Design (GRD) with nine treatments and two replication so there were 18 treatments. The treatment consists of AB1C1, AB1C2, AB1C3, AB2C1, AB2C2, AB2C3, AB3C1, AB3C2, and AB3C3. The research factors were variations of MOL banana weevil consisting of 0 ml (B1), 250 ml (B2), and 500 ml (B3), and bran variations consisting of 0 kg (C1), 0,25 kg (C2), and 0,5 kg (C3). The results showed that AB2C1 was the best treatment for the C-organic parameters (30,60%), Phosphorus (1,56%), and Potassium (0,99%), while AB3C3 was the best treatment for the C/N ratio parameters (26) and Nitrogen (1,36%). Keywords: bran, compost, MOL banana weevil, organic waste